(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The micellar extraction of thallium with krown-ether, carboxylic acids and azo-dyes into the phases of non-ionic surfactant OP-7 and neonol AF9-12 at cloud point temperature was investigated. The optimum conditions of micellar extraction of metal ion was established. The data was obtained enable to create procedure of atomic-absorption determination of thallium (III) in the natural water simple’s with micellar extraction pre-concentrating.